Furthering Trade and Investment in India’s Healthcare Sector. What Cost to the Public Health Care System? - Dalingwater, Louise (Revue Interventions économiques / Papers in Political Economy, 2026)
India is now the fifth largest global economy thanks to significant growth in exports and international exchange in recent years. The healthcare sector in India is one of the largest and fastest growing in terms of revenue and employment. It is however questionable to what extent increasing trade and investment in the health sector can effectively improve public health care delivery to the population, despite the importance of this critical sector . In line with the trade linkages special issue, this paper questions to what extent trade policy in health services is disembedded from the question of public health care provision. It is important to reiterate that protection of health systems implies engaging in issues beyond the pure economic agenda of countries wishing to further trade and investment. This paper thus takes a social constructivist approach to analyse the impact of the recent increase in trade and investment in the health sector in India. In particular, it draws on Ruggie’s concept of embedded liberalism to explore the potential effects of enhancing international trade and investment in this sector whilst still ensuring that sufficient welfare provisions are in place. It addresses two main questions: can domestic and international regulatory regimes ensure public health systems are protected and what are the trade offs to health care delivery of enhancing trade and investment with international private health care providers.